Costs and Factor Substitution in the Provision of Local Fire Services - Duncombe, William D. (The Review of Economics and Statistics, 1992)
Evidence on costs and factor substitution is presented for a sample of local fire departments in New York State. The results suggest that fire service production does not fit either Leontief, Cobb-Douglas, or CES technology. In addition, exogenous socioeconomic variables are found to significantly affect public-sector costs and the estimates of factor price elasticities. The findings of relatively low factor demand and substitution elasticities suggest that local governments may have limited flexibility in adjusting their production of fire services to minimize the impact of rising factor prices. Copyright 1992 by MIT Press.